2022
DOI: 10.1016/j.autrev.2021.103012
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and SARS-CoV2 infection: The spectrum from association to clinical implication: Report of the 15th Dresden Symposium on Autoantibodies

Abstract: The relation between infections and autoimmune diseases has been extensively investigated. Multiple studies suggest a causal relation between these two entities with molecular mimicry, hyperstimulation and dysregulation of the immune system as plausible mechanisms. The recent pandemic with a new virus, i.e. , SARS-CoV-2, has resulted in numerous studies addressing the potential of this virus to induce autoimmunity and, eventually, autoimmune disease. In addition, it has also revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…Molecular mimicry between COVID-19 viral epitopes and auto-epitope leading to autoAb production was initially suspected based on the use of bioinformatic models with linear sequence homology models, but with limited, if any, experimental evidence [ 86 ]. Indeed, cross-mimicry was not confirmed through competition experiments when using increased amounts of the autoantigen to test reactivity against SARS-Cov2, or vice versa when testing autoreactivity from a large panel of sera with organ and non-organ-specific autoimmune diseases in the presence SARS-Cov2 [ 87 ].…”
Section: Tolerance Breakdownmentioning
confidence: 99%
“…Molecular mimicry between COVID-19 viral epitopes and auto-epitope leading to autoAb production was initially suspected based on the use of bioinformatic models with linear sequence homology models, but with limited, if any, experimental evidence [ 86 ]. Indeed, cross-mimicry was not confirmed through competition experiments when using increased amounts of the autoantigen to test reactivity against SARS-Cov2, or vice versa when testing autoreactivity from a large panel of sera with organ and non-organ-specific autoimmune diseases in the presence SARS-Cov2 [ 87 ].…”
Section: Tolerance Breakdownmentioning
confidence: 99%
“…Similar to earlier work linking anti-cytokine antibodies to mycobacterial, staphylococcal and fungal diseases (32)(33)(34), autoantibodies against cytokines have been described in COVID-19. In particular, anti-type I Interferon antibodies distinguished ~10% of life-threatening pneumonia and ~20% of deaths from COVID-19 (6,35,36). Moreover, autoantibodies characteristic of systemic autoimmune disorders, such as anti-phospholipid antibodies, anti-nuclear antibodies and rheumatoid factor, were reported in COVID-19 (37)(38)(39)(40)(41).…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, while high antibody titre may be secondary to high levels of viral replication, it is also possible that antibodies that are generated by an extrafollicular B cell response are less potent and therefore, instead of neutralizing the virus efficiently, they may lead to disease pathogenesis by multiple mechanisms [ 135 ]. Extrafollicular B cell responses are also seen in systemic lupus erythematosus and such responses have shown to generate autoreactive antibodies, which is also a feature in COVID-19 [ 22 , 134 ]. Although the presence of extrafollicular B cell responses have not been studies in dengue infection, poorly neutralizing Nabs have shown to associate with severe disease [ 24 ].…”
Section: Introductionmentioning
confidence: 99%